2021
DOI: 10.1093/ageing/afab211
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive geriatric assessment in newly diagnosed older myeloma patients: a multicentre, prospective, non-interventional study

Abstract: Background Multiple myeloma is a disease of the older people, whose prognoses are highly heterogeneous. The International Myeloma Working Group (IMWG) proposed a geriatric assessment (GA) based on age, functional status and comorbidities to discriminate between fit and frail patients. Given the multidimensional nature of frailty and the relatively recent exploration of frailty in the field of MM, reaching a consensus on the measurement of frailty in MM patients remains challenging. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“… 10 The European Myeloma Network proposed that elderly MM patients should adopt different treatment intensities according to their fitness, 19 but currently the GA score is not widely used in the real world. The proportion of frail patients in our study was 35.78% (73/204) which was close to the report by Li et al 20 Our data suggested that GA score indicating fitness was independently correlated with longer OS, which was consistent with the conclusions in clinical trial. 10 In a retrospective study all the patients were treated with bortezomib‐based regimen and the frail patients had shorter OS compared with fit and moderate‐fit patients (49 months vs. 63 months vs.63 months, p < 0.05).…”
Section: Discussionsupporting
confidence: 92%
“… 10 The European Myeloma Network proposed that elderly MM patients should adopt different treatment intensities according to their fitness, 19 but currently the GA score is not widely used in the real world. The proportion of frail patients in our study was 35.78% (73/204) which was close to the report by Li et al 20 Our data suggested that GA score indicating fitness was independently correlated with longer OS, which was consistent with the conclusions in clinical trial. 10 In a retrospective study all the patients were treated with bortezomib‐based regimen and the frail patients had shorter OS compared with fit and moderate‐fit patients (49 months vs. 63 months vs.63 months, p < 0.05).…”
Section: Discussionsupporting
confidence: 92%
“…From a practical perspective, a sufficient level of geriatric assessment (GA) of elderly MM patients at diagnosis is also critical to account for all relevant comorbidities that may guide treatment. A recent multicenter prospective study suggests that a comprehensive GA (CGA) is warranted in newly diagnosed elderly MM patients and may provide some added benefit to assessing patient frailty compared to the International Myeloma Working Group (IMWG) recommendations [ 32 ]. In Finland, a survey study concluded that the majority of geriatricians utilized the CGA in their general practice, but only 11% of respondents incorporated all five domains in their CGA [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mini Nutritional Assessment-Short Form (MNA-SF) is a standard method to evaluate the nutritional status of the elderly. The Chinese version of MNA-SF performed well, and a score of 12–14 points is normal nutritional status, 8–11 points are at risk of malnutrition, and 0–7 points indicate malnutrition ( Amasene et al, 2021 ; Yao et al, 2022 ). Furthermore, intraoperative data (operation time, anesthetic time, and general anesthesia method) (intravenous, inhalation, or a combination of both ways) were accessed from medical records.…”
Section: Methodsmentioning
confidence: 98%